2-D modeling and simulation of fluidic microsystems for biological fluids analysis - Minas, Graça (2003)
This paper describes a fluid dynamic model that is suitable for accurate simulation of the on-chip liquid handling and mixing. The fluidic die (or mixer) is an integrated part of a biological microsystem for biological fluids analysis. It is designed for enabling a mixing process driven by diffusion, which allows an easy-to-fabricate and low-cost mixer. The fabrication is based on planar technology using OIC compatible lithography, which yields narrow channels in the vertical direction. Computer simulations have been carried out to analyze the details of the flow and the diffusion in the mixer in order to derive the appropriate design criteria for the layout. The mixer has been fabricated using glass micromachining and wafer-to-glass bonding. The performance is demonstrated using the fast-reaction of infinityTM uric acid reagent with urine samples.